Societal preferences for adjuvant melanoma health states: UK and Australia - Middleton, M; Atkins, M; Amos, K; Wang, P; Kotapati, S; Sabater, J; Beusterien, K (BioMed Central, 2017)
No studies have measured preference-based utility weights for specific toxicities and outcomes associated with approved and investigational adjuvant treatments for patients with resected high-risk melanoma.A cross-sectional study was conducted in the United Kingdom and Australia to obtain utilities for 14 adjuvant melanoma health states. One-on-one interviews were conducted using standard gamble; utility weights range from 0.0, dead, to 1.0, full health. Supplemental risk questions also were asked.Among 155 participants (52% male; mean age, 46 years) "adjuvant treatment no toxicities" (0.89) was most preferred, followed by "induction treatment" (0.88), and "no treatment" (0.86). Participants least preferred "cancer recurrence" (0.62); the utility for "cancer recurrence and 10-year survival with treatment" was 0.70. Disutilities for grade 2 toxicities ranged from -0.06 for fatigue to -0.13 for hypophysitis. The mean maximum acceptable risk of a life-threatening event ranged from 30% for a 6% increase in the chance of remaining cancer free over 3 years to 40% for an 18% increase; Australian respondents were willing to take higher risks.Reproducible health utilities for adjuvant melanoma health states were obtained from the general population in two countries. These utilities can be incorporated into treatment-specific cost-effectiveness evaluations.